Cover Feature: Target Identification of a 1, 3, 4‐Oxadiazin‐5(6H)‐One Anticancer Agent via Photoaffinity Labelling (Asian J. Org. Chem. 9/2019). Issue 9 (3rd September 2019) - Lim, Bumhee; Lee, Jinah; Kim, Byungjin; Lee, Rang; Park, Jaehyun; Oh, Dong‐Chan; Gam, Jongsik; Lee, Jeeyeon
Abstract : Photoaffinity labelling probes, OPALs, were rationally designed and synthesized to identify interacting protein targets of 1, 3, 4‐oxadiazin‐5(6H)‐one (LL‐2003). The labelling strategy enabled successful photo‐crosslinking with target proteins in both insect cell lysates and mammalian live cells, demonstrating the efficient and selective labelling of Src. A LC‐MS/MS analysis of the IGF‐1R overexpressed insect proteome labelled by OPALs identified the binding location of the synthesized probes. More information can be found in the Communication by Jeeyeon Lee et al. onpage 1626 in Issue 9, 2019 (DOI:10.1002/ajoc.201900258 ).